Gordon's Transfer Price Model for a Socialist Economy: A Comment. - Most, Kenneth S. (The Accounting Review, 1971)
Abstract This article comments on the proposed model by Myron J. Gordon for the transfer price problem using a socialist economy as the locus of inquiry. The problems posed by a bureaucratic organization, the need for some kind of sanctions, and the essentially subjective considerations underlying all pricing models are correctly identified as major obstacles in the way of a system which attempts to replicate a market economy without the constraints imposed by relative freedom of economic action. A fundamental weakness of Gordon's approach, however is its reliance on the neoclassical theory of the firm as an image from which such an investigation can proceed, and this is coupled with a specification that one of the conditions which the transfer price system must satisfy is that the prices approximate the characteristics of perfectly competitive prices, and have similar consequences for the allocation and utilization of resources. The article concludes that neither Gordon's model of the firm in a socialist economy, nor his postulated condition that prices must approximate to those which would obtain in a perfectly competitive market economy are acceptable approaches to the solution of the transfer price problem. The answer to this problem is urgently required in order that we may extend the boundaries of accounting to comprehend areas of economic activity which are, as yet, relatively unstructured. It will not be found, we suspect, to lie in the application of neoclassical price theory to problems which that theory was never intended to handle.